2015
DOI: 10.1080/14658011.2015.1110956
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, mechanical and biodegradation properties of pure, epoxidized and methoxylated castor oil based polyurethane

Abstract: A series of biodegradable polyurethane (BIOU) elastomers were obtained by chain extension of polyurethane (PU) prepolymer with the addition of castor oil (CAO), epoxidized CAO (ECAO) or methoxylated CAO (MCAO). The BIOU elastomers obtained were characterised by Fourier transform infrared, scanning electron microscopy, differential scanning calorimetry and tensile tester. The melting peak of BIOU became undetectable with an increase in the content of the chain extender regardless of its type. Some BIOU films, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Biopolyol produced from castor oil and NFS were purchased from Aladdin Industrial Co., Ltd. (Shanghai, China). Previous studies demonstrated that biopolyol derived from castor oil is biodegradable. With a high hydroxyl value of 137.81 ± 0.58 mg of KOH/g, castor oil is an ideal bio-based coating material. All of the chemical agents were analytical-grade and used directly as received.…”
Section: Methodsmentioning
confidence: 99%
“…Biopolyol produced from castor oil and NFS were purchased from Aladdin Industrial Co., Ltd. (Shanghai, China). Previous studies demonstrated that biopolyol derived from castor oil is biodegradable. With a high hydroxyl value of 137.81 ± 0.58 mg of KOH/g, castor oil is an ideal bio-based coating material. All of the chemical agents were analytical-grade and used directly as received.…”
Section: Methodsmentioning
confidence: 99%
“…However, it was reported that the biodegradation of poly(ester urethanes) and poly(ester-ether-urethanes) take place by hydrolysis of the ester linkages in flexible segments. 14,16 In addition, Umare and Chandure indicated that biodegradation occurs within urethane groups. 16 Unlike the addition of PUs, the biodegradation of condensation NIPUs occurs within the HSs.…”
Section: Resultsmentioning
confidence: 99%
“…14,16 In addition, Umare and Chandure indicated that biodegradation occurs within urethane groups. 16 Unlike the addition of PUs, the biodegradation of condensation NIPUs occurs within the HSs. The FTIR analysis suggested that biodegradation occurred in urea or urethane groups as confirmed by the pronounced reduction in the bands intensity or disappearance of N–H groups in urea and N–H of urethane.…”
Section: Resultsmentioning
confidence: 99%